CHROMOSOMAL ABNORMALITIES AND Y CHROMOSOME MICRODELETIONS IN BULGARIAN MALE WITH AZOOSPERMIA OR SEVERE OLIGOSPERMIA - Katya Kovacheva; Rumen Kotsev; Emiliana Konova; Violeta Rilcheva; Zornitsa Kamburova; Maria Simeonova (Peytchinski Publishing, 2018)
Male infertility is a complex disease, and genetic abnormalities are among the main causal factors for the disorder. Aim: In order to evaluate the proportion of the most common genetic factors in etiology of male infertility, examination for chromosomal abnormalities and microdeletions of Yq chromosome (delYq) was carried out in Bulgarian males with severe infertility. Materials and methods: The study was retrospective and involved a total of 142 infertile Bulgarian males (63 patients with azoospermia and 79 patients with severe oligozoospermia /sperm count < 5×106/ml), referred (2007-2016) for genetic testing, after preliminary examinations to exclude some more frequent causes for male infertility. Cytogenetic analysis by GTG-banding was carried out in 137 men, and molecular testing for AZF region microdeletions of Y chromosome by multiplex PCR was carried out in 109 men. Results: Chromosomal abnormalities were found in 16.8% of all investigated infertile men and the frequencies in patient subgroups with azoospermia and oligozoospermia were 20.7% (12/58) and 13.9% (11/79) respectively. The established frequency of delYq was 5.5% (6/109) in the overall group of infertile male and higher - 9.5% (6/63) in a subgroup of patients with azoospermia.The overall proportion of the two genetic factors was 30.2% in patients with azoospermia and 14% in men with oligozoospermia. In conclusion, chromosomal abnormalities and delYq account for about 22% of cases with severe infertility in Bulgarian men. Genetic testing should be a routine part of examinations in infertile males and along with genetic counseling; they provide an opportunity for the best choice of an appropriate technique for assisted reproduction of the couples.